A guiding framework for theory adaptation in operations management studies - Matolwandile M. Mtotywa; Tshidi Mohapeloa (Cogent Business & Management, 2023)
AbstractThe importance of theory cannot be overstated, as it is a primary research focus across most academic fields. This conceptual research study aimed to develop a guiding framework for theory adaptation in operations management studies. We logically developed a four-stage framework with a process flow and methodological approach to measurements. The framework conceptualizes the domain theory, problematizes the theory, and identifies the method theory for an alternative point of reference and required transition as well as identifies theory-strengthening influences. This is followed by the approach to the theory of unification with either integration or reconciliation. The framework then identifies the core tenets of the emergent theory and its boundaries based on value, time and space. The last stage is theory evaluation which ensures falsifiability of the theory to show that it is refutable. This last stage is based on operationally defined quantitative analysis for the variables, construct validity, convergence, discriminant, predictive and reliability, while for a relationship—linear or non-linear and examines logical and empirical adequacy. In addition to falsifiability, the theory must also be evaluated with the utility, which must ensure the theory’s scope, explanatory potential and predictive adequacy score. This study provides novel research as to the details of the framework of theory adaptation balancing the divergent objectives of the academia and practitioners and can be employed in operations management and other fields.